Carta dell’erosione del suolo del Lazio meridionale - Grauso, Sergio; Verrubbi, Vladimiro; Crovato, Cinzia; Zini, Alessandro; Peloso, Alessandro (GEOmedia, 2015)
The present work was aimed to test the operability of the RUSLE prediction model, on the basis of available data, in combination with different interpolation methods in the area of southern Lazio (central Italy). The work was based on published rainfall, soil, land-cover and elevation data archives and on a quick supplementary soil sampling survey. The RUSLE factors were computed by means of different correlation formulae and algorithms. Despite the lack of information data, the obtained soil erosion map can provide a useful reference frame of the soil loss potential for regional planning purposes.